2013
DOI: 10.1017/s0305000913000056
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of productive speech and language in Spanish-learning paediatric cochlear implant users

Abstract: It has been proposed that cochlear implant users may develop robust categorical perception skills, but that they show limited precision in perception. This article explores if a parallel contrast is observable in production, and if, despite acquiring typical linguistic representations, their early words are inconsistent. The participants were eight Spanish-learning deaf children implanted before their second birthday. Two studies examined the transition from babbling to words, and the one-word period. Study 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
(130 reference statements)
0
17
1
Order By: Relevance
“…In that study, no effect of syllable length in children with CI was found. It should be noted that syllable omissions from target words were not considered as variable productions in Moreno-Torres (2014). This may at least partly explain the discrepant findings of his study and ours.…”
Section: The Effect Of the Length Of Target Wordscontrasting
confidence: 66%
See 2 more Smart Citations
“…In that study, no effect of syllable length in children with CI was found. It should be noted that syllable omissions from target words were not considered as variable productions in Moreno-Torres (2014). This may at least partly explain the discrepant findings of his study and ours.…”
Section: The Effect Of the Length Of Target Wordscontrasting
confidence: 66%
“…Variability increased when target words contained more syllables in both groups of children. To the best of our knowledge, the only study that reported on the effect of word length on intraword variability in children with CI was Moreno-Torres (2014). In that study, no effect of syllable length in children with CI was found.…”
Section: The Effect Of the Length Of Target Wordsmentioning
confidence: 83%
See 1 more Smart Citation
“…Early access to sound enables 'early neural wiring' in the brain, which is advantageous for auditory and cognitive development, and which, in turn, will facilitate onset of babbling, a precursor for the development of spoken language (e.g. Schauwers et al, 2008;Moreno-Torres, 2014). Although the ability of the brain to adapt as a result of experience persists throughout life, certain changes are more predominant during the first few years of life (e.g.…”
Section: Early Implantation and Bilateral Inputmentioning
confidence: 99%
“…Children who have no secondary disabilities and receive unilateral CIs within the first three years of life often make relatively rapid progress in vocal development compared to younger, TD children (Ertmer & Jung, 2012;Ertmer & Mellon, 2001;Ertmer, Young, & Nathani, 2007;Fagan, 2015;Moreno-Torres, 2014;Schauwers, Gillis, Daemers, de Beukelaer, & Govaerts, 2004). This outcome is encouraging in that it suggests that children with profound HL are building a foundation for phonological development through exposure to auditory models and auditory feedback.…”
mentioning
confidence: 99%